Leadership and its influence in Malaysian IT firms - Sukhavasi, Snigdha (2010)
Three easily considered variables, culture, gender and size of an organization together illustrate the leadership styles in IT firms with regard to their influence on motivating the employees. Leadership studies in Malaysia have increased in the past decade, however the research carried out still appears quite limited. The results are achieved through qualitative research in the form of qualitative interviews, using the narrative approach, as part of a case study. The methodology was employed on the managers and employees from various IT firms on leadership. The findings do suggest that the size of the firm, the gender and culture influence the leadership motivational styles of a firm. It was discovered that Transformational/Transactional leadership was mostly used in the small-medium IT firms. Also many concerns regarding the subject surfaced in the process. Hence, the results have facilitated in discovering certain change that needs to be made and the issues where more emphasis needs to be placed. For instance, giving more importance to employee’s psychological needs emerges as the premier motivational force.